How artists can help us perceive organisational dysfunction and broken-ness differently - Wear, Andy (Organizational Aesthetics, 2024)
This paper considers what organizations might learn from the artist and the aesthetic devices they employ in the production of art that deals with dysfunction and broken-ness. By introducing these conditions as central to the redrawing of art’s remit following the existential crises and traumas of the 20th and 21st Centuries, it positions them as central to the critical contestation of what defines ‘functionality’ at an organisational level. From problematising the binarism of (and, consequently, the drawing of the boundary between) dysfunctional|functional and broken|fixed, I offer an organizational alternative as presented by artists. The work of German artist Joseph Beuys (1921-1986) and Venezuelan artist Alejandra Ghersi (1989-) has been carefully selected for the insights they offer to support this task. This paper explores their re-constitution of aesthetic registers (such as harmony, beauty, rhythm, and tone) as an organizational act, and positions the resulting ‘transformative dissonance’ as metaphor for a condition of post-binary organization. By focusing on each artist’s determined non-binarism and the associated aesthetic construct of their respective work, this paper presents approaches to dysfunction and broken-ness that accept dissonance as a natural organizational phenomenon, that then, from this (dis)position of acceptance, avail themselves to the pursuit of organizational transformation.